2020
DOI: 10.1017/s1368980020002876
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviour of Indonesian adolescents: a systematic review of the literature

Abstract: Objectives: Global evidence has shown that behaviour acquired during adolescence often lasts into adulthood. Diet quality of and malnutrition in Indonesian adolescents is a neglected area of research. The current study reviews all studies related to eating behaviour in Indonesian adolescents to support evidence-based policy to improve diets. Design: We searched electronic databases (six international and one local), from January 2000 to April 2018. The search terms used were (1) prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
2
17
1
7
Order By: Relevance
“…In this case, children at the age group of 3-9 years old have the highest percentage (above 50%) of consuming sweet foods once a day. Furthermore, about 98.4% of Indonesian teenagers at the age of 13-18 years old consumed nutritious foods including fruits and vegetables insufficiently (<400 g/day) [41]. The prevalence of overweight in Indonesia is the highest among adults by 8% of men and 29% of women suffering from central obesity [42].…”
Section: Food Consumption In Indonesiamentioning
confidence: 99%
“…In this case, children at the age group of 3-9 years old have the highest percentage (above 50%) of consuming sweet foods once a day. Furthermore, about 98.4% of Indonesian teenagers at the age of 13-18 years old consumed nutritious foods including fruits and vegetables insufficiently (<400 g/day) [41]. The prevalence of overweight in Indonesia is the highest among adults by 8% of men and 29% of women suffering from central obesity [42].…”
Section: Food Consumption In Indonesiamentioning
confidence: 99%
“…The DQI-A assessment was based on food-based dietary guidelines for adolescents, which put forward 3 basic principles for a healthy and balanced diet comprised of dietary quality, dietary diversity, and dietary equilibrium. 24 The DQI-A scoring utilized 9 recommended food groups consisting of (1) water; (2) bread and cereals; (3) grains and potatoes; (4) vegetables; (5) fruit; (6) milk products (7); cheese; (8) meat, fish, eggs, and substitutes; and (9) fat and oils.…”
Section: Data Collectionmentioning
confidence: 99%
“…4 The trend is projected to continue as Indonesian adolescents tend to have a high consumption of unhealthy foods (ie, western-style fast foods and convenience foods with excessive amounts of sodium). 7 In addition to poor diet quality, smoking habits also contribute to adolescents' poor quality of life, as 19.4% of Indonesian teenagers are active tobacco smokers. 8 This is of added concern considering the rise in smoking among the general population in Indonesia compared to other Southeast Asia countries.…”
Section: Introductionmentioning
confidence: 99%
“…Several Indonesian studies identified similar motives behind the adolescent's risky dietary behaviors. The individual factors including personal preferences, convenience and food price, together with environmental factors (mother's role, peer influence, food availability, school rules and socioeconomic status) were the reasons for their eating behavior (Rachmi et al, 2020;Sondari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study in Indonesia found that male adolescents more likely choose healthy food compared to women (Maulida et al, 2016). Despite the level of nutrition knowledge and awareness were quite good, adolescents were still lacking in self-efficacy (Rachmi et al, 2020). School as a medium to introduce healthier behaviors fails to fill in, particularly their absence on providing nutrition education (Savage et al, 2017) and nutritious food at school canteen (Ardzejewska et al, 2012;Mensink et al, 2012;Octaria et al, 2020).…”
Section: Introductionmentioning
confidence: 99%